Decode-STS: Deciphering the landscape of canine soft-tissue sarcoma using spatially defined proteomics and transcriptomics - D. Fuchs; E. Markkanen; H. Ech-Cherif; S. Aghaabbasi; A. Pöschel; E. Beebe; L. Laura; W. Wolski; F. Guscetti; M. Nolff (Journal of Comparative Pathology, 2025)

The Local Turn in a Global Sea: Identifying Sustainability Trade‐Offs in Regionalized Marine Aquaculture Systems - Gesche Krause; Ramón Filgueira; Nesar Ahmed; Karen A. Alexander; Furqan Asif; Lucia Fanning; Sebastian C. A. Ferse; Nike Fuchs; Jon Grant; Jordi Guillen; Christina Hörterer; Teresa R. Johnson; et al. (Reviews in Aquaculture, 2025)
Marine aquaculture, like the broader seafood industry, relies heavily on international trade and global supply chains for both production and sales. Recent global disruptions, including the COVID‐19 pandemic, the Russian invasion of Ukraine, the conflicts in the Middle East, and trade tensions, have exposed the social and economic vulnerabilities inherent in a globalized production system. In response, these events have sparked growing interest in transitioning to localized and regional supply chain models. Calls to “buy national” and support domestic economies highlight this trend toward regionalization. This study explores the sustainability implications of regionalizing marine aquaculture by examining the four key segments of the supply chain. These are (1) upstream inputs and resources (2) aquaculture production (3) downstream added value‐processing and (4) distribution–transportation. Potential benefits of regional production models include increased resilience to disruptions, lower transportation‐related carbon emissions, and support for local economies. However, such models may also introduce trade‐offs, including reduced production efficiency, supply and sales limitations, and implications for social, cultural, and governance structures. Our analysis reveals that the sustainability outcomes of regionalization are complex and context‐dependent. It is influenced by the specific characteristics of existing supply chains and the regional contexts in which they operate. While regionalization may offer advantages in certain contexts, it does not guarantee improved sustainability. Thus, it is crucial to critically assess the assumption that regionalization inherently leads to improved sustainability outcomes. Proactive evaluation of these dynamics is essential to develop strategies that maximize benefits while addressing potential trade‐offs.

A Review of Abrupt Permafrost Thaw: Definitions, Usage, and a Proposed Conceptual Framework - Hailey Webb; Matthias Fuchs; Benjamin W. Abbott; Thomas A. Douglas; Clayton D. Elder; Jessica Gilman Ernakovich; Eugenie S. Euskirchen; Mathias Göckede; Guido Grosse; Gustaf Hugelius; Miriam C. Jones; Charles Koven; et al. (Current Climate Change Reports, 2025)
Purpose of Review We review how ‘abrupt thaw’ has been used in published studies, compare these definitions to abrupt processes in other Earth science disciplines, and provide a definitive framework for how abrupt thaw should be used in the context of permafrost science. Recent Findings We address several aspects of permafrost systems necessary for abrupt thaw to occur and propose a framework for classifying permafrost processes as abrupt thaw in the future. Based on a literature review and our collective expertise, we propose that abrupt thaw refers to thaw processes that lead to a substantial persistent environmental change within a few decades. Abrupt thaw typically occurs in ice-rich permafrost but may be initiated in ice-poor permafrost by external factors such as hydrologic change (i.e., increased streamflow, soil moisture fluctuations, altered groundwater recharge) or wildfire. Summary Permafrost thaw alters greenhouse gas emissions, soil and vegetation properties, and hydrologic flow, threatening infrastructure and the cultures and livelihoods of northern communities. The term ‘abrupt thaw’ has emerged in scientific discourse over the past two decades to differentiate processes that rapidly impact large depths of permafrost, such as thermokarst, from more gradual, top-down thaw processes that impact centimeters of near-surface permafrost over years to decades. However, there has been no formal definition for abrupt thaw and its use in the scientific literature has varied considerably. Our standardized definition of abrupt thaw offers a path forward to better understand drivers and patterns of abrupt thaw and its consequences for global greenhouse gas budgets, impacts to infrastructure and land-use, and Arctic policy- and decision-making.

Human endothelial colony forming cells (ECFCs) require endothelial protein C receptor (EPCR) for cell cycle progression and angiogenic activity - Sarah E. J. Chambers; Jasenka Guduric-Fuchs; Edoardo Pedrini; Pietro M. Bertelli; Chutima Charoensuk; Elisa Peixoto; Varun Pathak; Hamza I. Alhamdan; Ruoxiao Xie; Anna Krasnodembskaya; Judith Lechner; Alan W. Stitt; et al. (Angiogenesis, 2025)
Vascular repair and regeneration are critical for tissue homeostasis. Endothelial colony forming cells (ECFCs) are vessel-resident progenitors with vasoreparative capacity and they offer an important avenue for allogeneic cytotherapy to achieve perfusion of ischemic tissues. Endothelial Protein C Receptor (EPCR) has been proposed as a marker for vascular endothelial stem cells, but its precise role in ECFC biology remains unknown. The current study has investigated the biological relevance of EPCR in ECFC function. Our data show that over 95% of ECFCs exhibit high EPCR expression. These levels surpassing CD34 and CD157, positions EPCR as a new robust ECFC immunophenotypic marker, alongside established markers CD31 and CD105. Functionally, depleting EPCR expression in ECFCs significantly diminished angiogenic activity, including proliferation, migration and tube formation. This knockdown also altered normal ECFC barrier function. Transcriptomic analysis indicated that knockdown of EPCR led to enrichment of gene signatures for cell cycle, TGF beta, and focal adhesion kinases. G1 cell cycle arrest was confirmed in ECFCs with depleted EPCR. Mechanistically, EPCR knockdown led to increased release of TGFβ2 and SMAD2/3 activation, coupled with increased p21, decreased pFAK, and increased transgelin. Additionally, we showed that quiescent ECFCs showed significantly lower EPCR expression when compared to proliferating ECFCs. In agreement with this, cell sorting experiments demonstrated that ECFCs with the highest EPCR expression exhibited the highest clonogenic capacity. In summary, our findings highlight that EPCR expression in ECFCs is critical for their angiogenic activity, by modulating cell cycle progression. Graphical abstract

Reconciling Gene Tree Discordance and Biogeography in European Crows - Chyi Yin Gwee; Dirk Metzler; Jérôme Fuchs; Jochen B. W. Wolf (Molecular Ecology, 2025)
Reconstructing the evolutionary history of young lineages diverging with gene flow is challenging due to factors like incomplete lineage sorting, introgression, and selection causing gene tree discordance. The European crow hybrid zone between all‐black carrion crows and grey‐coated hooded crows exemplifies this challenge. Most of the genome in Western and Central European carrion crow populations is near‐identical to hooded crows, but differs substantially from their Iberian congeners. A notable exception is a single major‐effect colour‐locus under sexual selection aligning with the ‘species’ tree. To understand the underlying evolutionary processes, we reconstructed the biogeographic history of the species complex. During the Pleistocene carrion and hooded crows took refuge in the Iberian Peninsula and the Middle East, respectively. Allele‐sharing of all‐black Western European populations with likewise black Iberian crows at the colour‐locus represents the last trace of carrion crow ancestry, resisting gene flow from expanding hooded crow populations that have homogenised most of the genome. A model of colour‐locus introgression from an Iberian ancestor into hooded crow populations near the Pyrenées was significantly less supported. We found no positive relationship between introgression and recombination rate consistent with the absence of genome‐wide, polygenic barriers in this young species complex. Overall, this study portrays a scenario where few large‐effect loci, subject to divergent sexual selection, resist rampant and asymmetric gene exchange. This study underscores the importance of integrating population demography and biogeography to accurately interpret patterns of gene tree discordance following population divergence.

Quaternary intensification of spine epibiosis in the cidaroid echinoid Eucidaris: implications for anthropogenic impacts - Elizabeth Petsios; Corinne E. Fuchs; Michal Kowalewski; Paul Larson; Roger W. Portell; Carrie L. Tyler (Frontiers in Marine Science, 2025)
Echinoids are an integral part of present-day and ancient marine trophic webs, and they host a variety of mutualistic, commensalistic, and parasitic epibionts on their spines and test. Cidaroid echinoid (slate pencil urchins) spines in particular are commonly colonized by epizoans. Eucidaris in the western Atlantic and eastern Pacific today are notable for the frequency and intensity of calcifying, non-calcifying, and galling colonization on their spines. While moderate levels of spine colonization may provide camouflage and other benefits to the host, a high density of encrusters may instead reduce host fitness, and galling is invariably parasitic. Significant environmental changes in the equatorial and sub-equatorial western Atlantic and eastern Pacific necessitate a paleobiological approach to constrain the timing of changes in epibiosis intensity on Eucidaris . Here, we compare rates of spine colonization in present-day Eucidaris populations with ancestral Pliocene Eucidaris assemblages. We find that Pliocene spines show no evidence of parasitic galling, and significantly less evidence of epibiosis than their present-day descendants in both the Atlantic and Pacific. This holds true even after accounting for taphonomic processes that would preferentially erase evidence of non-calcifying colonization. We propose that the high intensity of colonization on present-day Eucidaris spines is a relatively recent development and may reflect human-induced habitat degradation in the region, underscoring the need for further investigation into this biotic interaction.

Effectiveness of ozone nanobubble treatments on high biomass cyanobacterial blooms: A mesocosm experiment and field trial - Justin D. Chaffin; David E. Berthold; Eugene C. Braig; Josh D. Fuchs; Rachel S. Gabor; Stephen J. Jacquemin; Haley E. Kuhn; Lillian D. Labus; H. Dail Laughinghouse; Forrest W. Lefler; Heath E. Mash; Heather A. Raymond; et al. (Journal of Environmental Management, 2024)

Long sediment-laden algal turf likely impairs coral recovery on Florida’s coral reefs - A. Duran; K. E. Speare; C. Fuchs; T. C. Adam; L. Palma; M. W. Miller; L. Collado-Vides; A. R. Harborne; D. E. Burkepile (Coral Reefs, 2024)

Impacts of irregularly-distributed acidified brine flow on geo-chemo-mechanical alteration in an artificial shale fracture under differential stress - Samantha J. Fuchs; Dustin Crandall; Johnathan E. Moore; Mayandi Sivaguru; Bruce W. Fouke; D. Nicolas Espinoza; Ange-Therese Akono; Charles J. Werth (International Journal of Greenhouse Gas Control, 2024)

GEMAS: Chemical weathering of silicate parent materials revealed by agricultural soil of Europe - Philippe Négrel; Anna Ladenberger; Clemens Reimann; Alecos Demetriades; Manfred Birke; Martiya Sadeghi; S. Albanese; M. Andersson; R. Baritz; M.J. Batista; A. Bel-lan; D. Cicchella; et al. (Chemical Geology, 2023)

Improving nitrogen use efficiency in irrigated cotton production - Clemens Scheer; David W. Rowlings; Diogenes L. Antille; Massimiliano De Antoni Migliorati; Kathrin Fuchs; Peter R. Grace (Nutrient Cycling in Agroecosystems, 2023)
Irrigated cotton in Australia is mainly grown on heavy textured soils which are prone to waterlogging, resulting in significant losses of nitrogen (N) via denitrification and surface run-off. This study investigated fertiliser nitrogen use efficiency (fNUE) over three seasons on five commercial cotton farms using the 15 N tracer technique. Fertiliser NUE was consistently low across all fertilised treatments, with on average 47% of the applied fertiliser lost and only 17% of the N taken up by the crop derived from fertiliser. There was no significant effect of different N fertiliser products and rates on cotton lint yield. High lint yields (0.9–3.6 Mg ha −1 ) could be achieved even without the application of N fertiliser, demonstrating mineralisation of soil organic N, residual fertiliser, or N returned with crop residues, as key source of N in these cropping systems. Using the nitrification inhibitor DMPP and overhead instead of furrow irrigation showed potential to reduce N fertiliser losses. The results demonstrate that under current on-farm management fNUE is low on irrigated cotton farms in Australia and highlight the need to account for soil N stocks and mineralisation rates when assessing optimized fertiliser rates. There is substantial scope to improve fNUE and reduce N losses without any impact on lint yield, by adjusting N fertiliser application rates, in particular in combination with the use of the nitrification inhibitor DMPP. Using overhead instead of furrow irrigation is a promising approach to improve not only water use efficiency, but also fNUE in irrigated cotton systems.

HIV-related drivers of sexual compulsivity and sexuality in sexual minority men who use methamphetamine - Hema R. Kondur; Tae K. Lee; Roger McIntosh; Hetta Gouse; Robert Paul; Christian Grov; Dietmar Fuchs; Walter Gómez; Samantha E. Dilworth; Torsten B. Neilands; Adam W. Carrico (Journal of NeuroVirology, 2022)

Full Parameterisation Matters for the Best Performance of Crop Models: Inter-comparison of a Simple and a Detailed Maize Model - A. M. Manschadi; J. Eitzinger; M. Breisch; W. Fuchs; T. Neubauer; A. Soltani (International Journal of Plant Production, 2021)
Process-based crop growth models have become indispensable tools for investigating the effects of genetic, management, and environmental factors on crop productivity. One source of uncertainty in crop model predictions is model parameterization, i.e. estimating the values of model input parameters, which is carried out very differently by crop modellers. One simple (SSM-iCrop) and one detailed (APSIM) maize ( Zea mays L.) model were partially or fully parameterized using observed data from a 2-year field experiment conducted in 2016 and 2017 at the UFT (Universitäts- und Forschungszentrum Tulln, BOKU) in Austria. Model initialisation was identical for both models based on field measurements. Partial parameterization (ParLevel_1) was first performed by estimating only those parameters related to crop phenology. Full parameterization (ParLevel_2) was then conducted by estimating parameters related to phenology plus those affecting dry mass production and partitioning, nitrogen uptake, and grain yield formation. With ParLevel_1, both models failed to provide accurate estimation of LAI, dry mass accumulation, nitrogen uptake and grain yield, but the performance of APSIM was generally better than SSM-iCrop. Full parameterization greatly improved the performance of both crop models, but it was more effective for the simple model, so that SSM-iCrop was equally well or even better compared to APSIM. It was concluded that full parameterization is indispensable for improving the accuracy of crop model predictions regardless whether they are simple or detailed. Simple models seem to be more vulnerable to incomplete parameterization, but they better respond to full parameterization. This needs confirmation by further research.

Tryptophan depletion predicts lower positive affect in sexual minority men living with HIV who use methamphetamine - Ji-Young Lee; Tiffany R. Glynn; Judith T. Moskowitz; Dietmar Fuchs; Torsten B. Neilands; Samantha E. Dilworth; Daniel J. Feaster; Allan Rodriguez; Adam W. Carrico (Journal of NeuroVirology, 2021)

Tryptophan degradation is associated with risk-taking propensity in methamphetamine users with treated HIV infection - Jared Lee; Ji-Young Lee; Christina S. Meade; Michael Cohn; Antonio Chahine; Samantha E. Dilworth; Jessica F. Magidson; Hetta Gouse; Dietmar Fuchs; Adam W. Carrico (Journal of NeuroVirology, 2020)

Validation of a KHV antibody enzyme‐linked immunosorbent assay (ELISA) - S M Bergmann; Q Wang; W Zeng; Y Li; Y Wang; M Matras; M Reichert; D Fichtner; M Lenk; T Morin; N J Olesen; H F Skall; et al. (Journal of Fish Diseases, 2017)
Koi herpesvirus ( KHV ) causes KHV disease ( KHVD ). The virus is highly contagious in carp or koi and can induce a high mortality. Latency and, in some cases, a lack of signs presents a challenge for virus detection. Appropriate immunological detection methods for anti‐ KHV antibodies have not yet been fully validated for KHV . Therefore, it was developed and validated an enzyme‐linked immunosorbent assay ( ELISA ) to detect KHV antibodies. The assay was optimized with respect to plates, buffers, antigens and assay conditions. It demonstrated high diagnostic and analytical sensitivity and specificity and was particularly useful at the pond or farm levels. Considering the scale of the carp and koi industry worldwide, this assay represents an important practical tool for the indirect detection of KHV , also in the absence of clinical signs.

Paleolimnological features of a mega-lake phase in the Makgadikgadi Basin (Kalahari, Botswana) during Marine Isotope Stage 5 inferred from diatoms - Mareike Schmidt; Markus Fuchs; Andrew C. G. Henderson; Annette Kossler; Melanie J. Leng; Anson W. Mackay; Elisha Shemang; Frank Riedel (Journal of Paleolimnology, 2017)

Visualization of tumor heterogeneity by in situ padlock probe technology in colorectal cancer - Amin El-Heliebi; Karl Kashofer; Julia Fuchs; Stephan W. Jahn; Christian Viertler; Andrija Matak; Peter Sedlmayr; Gerald Hoefler (Histochemistry and Cell Biology, 2017)

Capulavirus and Grablovirus: two new genera in the family Geminiviridae - Arvind Varsani; Philippe Roumagnac; Marc Fuchs; Jesús Navas-Castillo; Enrique Moriones; Ali Idris; Rob W. Briddon; Rafael Rivera-Bustamante; F. Murilo Zerbini; Darren P Martin (Archives of Virology, 2017)

The amino-terminal domain of ORF149 of koi herpesvirus is preferentially targeted by IgM from carp populations surviving infection - F. Torrent; A. Villena; P. A. Lee; W. Fuchs; S. M. Bergmann; J. M. Coll (Archives of Virology, 2016)

Assessing the influence of historic net and gross land changes on the carbon fluxes of Europe - Richard Fuchs; Catharina J. E. Schulp; Geerten M. Hengeveld; Peter H. Verburg; Jan G. P. W. Clevers; Mart‐Jan Schelhaas; Martin Herold (Global Change Biology, 2016)
Legacy effects of land cover/use on carbon fluxes require considering both present and past land cover/use change dynamics. To assess past land use dynamics, model‐based reconstructions of historic land cover/use are needed. Most historic reconstructions consider only the net area difference between two time steps (net changes) instead of accounting for all area gains and losses (gross changes). Studies about the impact of gross and net land change accounting methods on the carbon balance are still lacking. In this study, we assessed historic changes in carbon in soils for five land cover/use types and of carbon in above‐ground biomass of forests. The assessment focused on Europe for the period 1950 to 2010 with decadal time steps at 1‐km spatial resolution using a bookkeeping approach. To assess the implications of gross land change data, we also used net land changes for comparison. Main contributors to carbon sequestration between 1950 and 2010 were afforestation and cropland abandonment leading to 14.6 PgC sequestered carbon (of which 7.6 PgC was in forest biomass). Sequestration was highest for old‐growth forest areas. A sequestration dip was reached during the 1970s due to changes in forest management practices. Main contributors to carbon emissions were deforestation (1.7 PgC) and stable cropland areas on peaty soils (0.8 PgC). In total, net fluxes summed up to 203 TgC yr −1 (98 TgC yr −1 in forest biomass and 105 TgC yr −1 in soils). For areas that were subject to land changes in both reconstructions (35% of total area), the differences in carbon fluxes were about 68%. Overall for Europe the difference between accounting for either gross or net land changes led to 7% difference (up to 11% per decade) in carbon fluxes with systematically higher fluxes for gross land change data.

Approach to Cerebrospinal Fluid (CSF) Biomarker Discovery and Evaluation in HIV Infection - Richard W. Price; Julia Peterson; Dietmar Fuchs; Thomas E. Angel; Henrik Zetterberg; Lars Hagberg; Serena Spudich; Richard D. Smith; Jon M. Jacobs; Joseph N. Brown; Magnus Gisslen (Journal of Neuroimmune Pharmacology, 2013)

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

Diabetes and risk of pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium - Joanne W. Elena; Emily Steplowski; Kai Yu; Patricia Hartge; Geoffrey S. Tobias; Michelle J. Brotzman; Stephen J. Chanock; Rachael Z. Stolzenberg-Solomon; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Kathy Helzlsouer; Eric J. Jacobs; et al. (Cancer Causes & Control, 2013)

An in vivo neovascularization assay for screening regulators of angiogenesis and assessing their effects on pre-existing vessels - Witold W. Kilarski; Ludvig Petersson; Peder Fredlund Fuchs; Marcin S. Zielinski; Pär Gerwins (Angiogenesis, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

New insights into the role of angiotensin-converting enzyme obtained from the analysis of genetically modified mice - Xiao Z. Shen; Hong D. Xiao; Ping Li; Chentao X. Lin; Sandrine Billet; Derick Okwan-Duodu; Jon W. Adams; Ellen A. Bernstein; Yi Xu; Sebastien Fuchs; Kenneth E. Bernstein (Journal of Molecular Medicine, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Power matters in closing the phenotyping gap - Carola W. Meyer; Ralf Elvert; André Scherag; Nicole Ehrhardt; Valerie Gailus-Durner; Helmut Fuchs; Helmut Schäfer; Martin Hrabé de Angelis; Gerhard Heldmaier; Martin Klingenspor (The Science of Nature, 2007)

Effects of increased cellular zinc levels on gene and protein expression in HT-29 cells - Birgit Kindermann; Frank Döring; Dagmar Fuchs; Michael W. Pfaffl; Hannelore Daniel (BioMetals, 2005)

Untersuchung von Jägern und Schwarzwild auf die Seroprävalenz von Antikörpern gegenüberLeptospira interrogans in Südostösterreich - A. Deutz; K. Fuchs; W. Schuller; Maria Müller; Ursula Kerbl; Charlotte Klement (European Journal of Wildlife Research, 2002)

Apamin-sensitive, small-conductance, calcium-activated potassium channels mediate cholinergic inhibition of chick auditory hair cells - W. A. Yuhas; P. A. Fuchs (Journal of Comparative Physiology A, 1999)

Presence of Staphylococcus aureus with Reduced Susceptibility to Vancomycin in Germany - G. Bierbaum; K. Fuchs; W. Lenz; C. Szekat; H. -G. Sahl (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Xanthine oxidase inhibition by allopurinol affects the reliability of urinary caffeine metabolic ratios as markers for N -acetyltransferase 2 and CYP1A2 activities - P. Fuchs; W. E. Haefeli; H. R. Ledermann; M. Wenk (European Journal of Clinical Pharmacology, 1999)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Identification and transcriptional analysis of pseudorabies virus UL6 to UL12 genes - J. M. Dijkstra; W. Fuchs; T. C. Mettenleiter; B. G. Klupp (Archives of Virology, 1997)

Gametic differentiation in Chlamydomonas reinhardtii: light dependence and gene expression patterns - Ulrike Treier; Sabine Fuchs; Martina Weber; Warren W. Wakarchuk; Christoph F. Beck (Archives of Microbiology, 1989)

Enzyme reactions involved in anaerobic cyclohexanol metabolism by a denitrifying Pseudomonas species - W. Dangel; A. Tschech; G. Fuchs (Archives of Microbiology, 1989)

Occurrence of corrinoid-containing membrane proteins in anaerobic bacteria - W. Dangel; H. Schulz; G. Diekert; H. Knig; G. Fuchs (Archives of Microbiology, 1987)

Introduction and establishment ofApanteles flavipes [Hym.: Braconidae] onDiatraea saccharalis [Lep.: Pyralidae] in texas - T. W. Fuchs; F. R. Huffman; J. W. Smith (BioControl, 1979)

Carbon isotope fractionation by Methanobacterium thermoautotrophicum - G. Fuchs; R. Thauer; H. Ziegler; W. Stichler (Archives of Microbiology, 1979)

Bacterial breakdown of benomyl. II. Mixed cultures - A. Fuchs; F. W. de Vries (Antonie van Leeuwenhoek, 1978)

Bacterial breakdown of benomyl. I. Pure cultures - A. Fuchs; F. W. de Vries (Antonie van Leeuwenhoek, 1978)

Translocation, distribution and metabolism of triforine in plants - A. Fuchs; W. Ost (Archives of Environmental Contamination and Toxicology, 1976)

Elektronenmikroskopische Darstellung peroxydatischer Aktivitten bei Phaseolus vulgaris nach Infektion mit Uromyces phaseoli typica - K. Mendgen; W. H. Fuchs (Archives of Microbiology, 1973)

Die Ultrastruktur des Penetrationsvorganges von Olpidium brassicae an Kohlrabi-Wurzeln - D. E. Lesemann; W. H. Fuchs (Archives of Microbiology, 1970)

Elektronenmikroskopische Untersuchung ber die Vorbereitung der Infektion in encystierten Zoosporen von Olpidium brassicae - D. E. Lesemann; W. H. Fuchs (Archives of Microbiology, 1970)

Der Infektionsvorgang bei Polymyxa betae - B. Keskin; W. H. Fuchs (Archives of Microbiology, 1969)

Pyridoxin-abhngige Vernderungen im chemischen Aufbau der Hyphen vonNeurospora sitophila - H. Aurich; W. Neumann; U. Fuchs (Archives of Microbiology, 1968)

Weiteres zur Keimungsphysiologie von Puccinia graminis tritici (Pers.) Erickss. u. Henn - A. Gaertner; W. H. Fuchs (Archives of Microbiology, 1962)

Zur Morphologie von Olpidium brassicae (Wor.) Dangeard - Sehinaz Sahtiyanci; A. Gaertner; W. H. Fuchs (Archives of Microbiology, 1960)

Weiteres zur Keimungsphysiologie von Puccinia graminis tritici (Pers.) Erickss. u. Henn. - A. Gaertner; W. H. Fuchs (Archives of Microbiology, 1960)

ber den Einflu von Chinonoximbenzoylhydrazon auf das Wachstum von Bacillus subtilis - W. H. Fuchs; H. Metz (Archives of Microbiology, 1958)

Untersuchungen zur Keimungsphysiologie des Schwarzrostes Puccinia graminis tritici (Pers.) Erickss. u. Henn - W. H. Fuchs; A. Gaertner (Archives of Microbiology, 1957)